2021
DOI: 10.33448/rsd-v10i2.12349
|View full text |Cite
|
Sign up to set email alerts
|

O impacto das relações familiares no comportamento suicida

Abstract: Objetivo: Analisar o impacto das relações familiares no comportamento suicida. Metodologia: Pesquisa exploratória, descritiva, abordagem qualitativa, realizada de dezembro de 2017 a novembro de 2019 em Unidade de Pronto Atendimento de Assis/SP. Entrevistas realizadas com pessoas com tentativa de suicídio. Empregou-se referencial metodológico de Análise de Conteúdo. Projeto de pesquisa aprovado pelo Comitê de Ética em Pesquisa. Resultados: Entrevistados 113 participantes de total de 309 ocorrências de tentativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
8
0
4
Order By: Relevance
“…Being exposed to an environment in which young people experience displacement and a sense of not belonging contributes to the occurrence of suicidal behavior in adolescents. (14,20) On the other hand, there are studies that show that satisfaction in interpersonal relationships, especially with the family, is a very important protective factor for suicide attempts, since the offered family support has the potential to decrease the psychological impact of difficult situations faced by the individual. (20) A review study identified that the most common protective factors for both suicide and bullying were being female, having good mental health, belonging to a two-parent family, safe school environment, good family relationships and having an involved teacher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being exposed to an environment in which young people experience displacement and a sense of not belonging contributes to the occurrence of suicidal behavior in adolescents. (14,20) On the other hand, there are studies that show that satisfaction in interpersonal relationships, especially with the family, is a very important protective factor for suicide attempts, since the offered family support has the potential to decrease the psychological impact of difficult situations faced by the individual. (20) A review study identified that the most common protective factors for both suicide and bullying were being female, having good mental health, belonging to a two-parent family, safe school environment, good family relationships and having an involved teacher.…”
Section: Discussionmentioning
confidence: 99%
“…(14,20) On the other hand, there are studies that show that satisfaction in interpersonal relationships, especially with the family, is a very important protective factor for suicide attempts, since the offered family support has the potential to decrease the psychological impact of difficult situations faced by the individual. (20) A review study identified that the most common protective factors for both suicide and bullying were being female, having good mental health, belonging to a two-parent family, safe school environment, good family relationships and having an involved teacher. (21) The use of alcohol and drugs also presents itself as a risk factor, as shown by Neto and Pelizzari, who, after researching the medical records of young people followed-up in a Psychosocial Care Center for Alcohol and Other Drugs (CAPS AD, as per itis Portuguese acronym), with ages between 12 and 18 years, found that 97% of the records analyzed with complaints of suicide attempts were related to alcoholic ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Os profissionais também devem oferecer auxílio e apoio aos cuidadores, que se sentem culpados pela situação. O contexto familiar pode exercer um papel colaborativo e protetor, além de ser um reforço junto aos profissionais no manejo de adolescentes em situação de comportamento suicida Marcolan, 2021).…”
Section: Caps (To12)unclassified
“…Suicidal behavior includes suicidal ideation, suicide attempts and suicide itself, with a focus on the worrying increase in suicide deaths and the still worrying number of suicide attempts. The prevalence is higher in the general population (Silva & Marcolan, 2021). Suicidal behaviour is described as an action in which the person causes self-harm with no apparent justification or fear of dying.…”
Section: Introductionmentioning
confidence: 99%